An Unconventional Inchworm Actuator Based on PZT/ERFs Control Technology - Guojun Liu; Yanyan Zhang; Jianfang Liu; Jianqiao Li; Chunxiu Tang; Tengfei Wang; Xuhao Yang (Applied Bionics and Biomechanics)
An unconventional inchworm actuator for precision positioning based on piezoelectric (PZT) actuation and electrorheological fluids (ERFs) control technology is presented. The actuator consists of actuation unit (PZT stack pump), fluid control unit (ERFs valve), and execution unit (hydraulic actuator). In view of smaller deformation of PZT stack, a new structure is designed for actuation unit, which integrates the advantages of two modes (namely, diaphragm type and piston type) of the volume changing of pump chamber. In order to improve the static shear yield strength of ERFs, a composite ERFs valve is designed, which adopts the series-parallel plate compound structure. The prototype of the inchworm actuator has been designed and manufactured in the lab. Systematic test results indicate that the displacement resolution of the unconventional inchworm actuator reaches 0.038 μm, and the maximum driving force and velocity are 42 N, 14.8 mm/s, respectively. The optimal working frequency for the maximum driving velocity is 120 Hz. The complete research and development processes further confirm the feasibility of developing a new type of inchworm actuator with high performance based on PZT actuation and ERFs control technology, which provides a reference for the future development of a new type of actuator.